2004
DOI: 10.1021/bc049838s
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anti-Rotavirus Action of Human Cystatin C by Site-Specific Glycosylation in Yeast

Abstract: The cDNA encoding human cystatin C (HCC) was subjected to site-specific substitution of alanine for serine at the position 37, to obtain the Asn(35)-Lys(36)-Ser(37) sequence that is a signal for asparagine-linked (N-linked) glycosylation of protein in eukaryotes, and was transformed into Pichia pastoris X33. As a result, 1.2 mg/L oligomannosyl HCC with a carbohydrate chain of Man(10)GlcNAc(2) was produced by the Pichia transformant. The oligomannosyl HCC was more stable at the low ionic strength condition of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Post-translational modifications are known to have an impact on the IgE-binding activity [10]. The Pichia pastoris system has been used to study sitespecific glycosylations and enhancement of the molecular stability of recombinant proteins [11]. The number of mannose residues ('high-mannosylation' -glycosylation pattern) added to P. pastoris recombinant glycoproteins are mainly Man 8 GlcNAc 2 and Man 9 GlcNAc 2 .…”
mentioning
confidence: 99%
“…Post-translational modifications are known to have an impact on the IgE-binding activity [10]. The Pichia pastoris system has been used to study sitespecific glycosylations and enhancement of the molecular stability of recombinant proteins [11]. The number of mannose residues ('high-mannosylation' -glycosylation pattern) added to P. pastoris recombinant glycoproteins are mainly Man 8 GlcNAc 2 and Man 9 GlcNAc 2 .…”
mentioning
confidence: 99%
“…Both hcC and cC are nonglycosylated proteins. It had been reported that the anti‐rotavirus activity of hcC was substantially enhanced by site‐directed glycosylation using the yeast expression system (Nakamura et al 2004). Likewise, N ‐glycosylation at Asn106 greatly improved the freezing stability of recombinant cC over‐expressed in yeast Pichia.…”
mentioning
confidence: 99%
“…Two synthetic genes encoding the primary amino acid sequences of HSA and HSB were prepared using overlap‐extension PCR , as illustrated in Fig. .…”
Section: Methodsmentioning
confidence: 99%